New insights into hydrological exchange between the South China Sea and the Western Pacific Ocean based on the Nd isotopic composition of seawater. (December 2015) - Wu, Qiong; Colin, Christophe; Liu, Zhifei; Douville, Eric; Dubois-Dauphin, Quentin; Frank, Norbert
Abstract: Rare Earth Element (REE) concentrations and Nd isotopic compositions (εNd) of 16 seawater profiles collected in the northern South China Sea (SCS) and the Philippine Sea were investigated (1) to establish the distribution of the Nd isotopic composition of water masses along the tropical Western Pacific and the SCS until now underexplored, (2) to constrain hydrological exchanges between the SCS and the Philippine Sea through the Luzon Strait, and (3) to test, in the context of the semi-closed marginal sea (SCS), the possible impact of the process of exchange of Nd between SCS water masses and unradiogenic sediments from its north-western margin. εNd values for mid- and deep-water masses of the Philippine Sea and the SCS range from −2.3 to −4.4 and generally increase slightly as water depth increases. In the Philippine Sea, εNd values for the North Pacific Intermediate Water (NPIW) reach −2.7±0.4 at mid-depths (500 to 1400 m). Below ~1800 m, the Pacific Deep Water (PDW) is characterised by less radiogenic Nd (−4.1±0.5) indicating the intrusion of southern-sourced water. For most of the stations in the Northern SCS, water masses below 1500 m (PDW) display homogenous εNd values (~−4.1) identical to those of the PDW in the Philippine Sea. εNd values for the South China Sea Intermediate Water (SCSIW, 500–1500 m) vary from −3.0 to −3.9 as a result of the vertical mixing of the NPIW with the PDW in the SCS. Seawater εNd values for the SCS display local modification (~−5.3 to −7.0) in areas where water passes above sediment drift deposit systems. This implies locally confined "boundary exchange'' with unradiogenic sediments (around −11) insufficient to alter the Nd isotopic composition of the PDW in the Northern SCS. In addition, εNd values analysed for the first time in nepheloid layers collected along the north-western margin of the SCS do not exhibit any significant modification of the seawater εNd which remains into a narrow range between −3.7 and −4.3, similar to that of the PDW. A compilation of εNd from the sea surface water of the SCS indicates lower εNd values in the western and the central SCS (−3.3 to −9.5), induced by sediments riverine input which are characterised by unradiogenic εNd (around −11). Finally, as significant variations are observed in seawater εNd at mid-depth between the SCS and the Philippine Sea, εNd values could be used in the future to track intermediate water mass exchange in the Luzon Strait, a process which, at present, remains poorly understood.